SOCIAL STATUS OF FARMERS AND LABOUR UTILIZATION PATTERN IN INTENSIVE REARING OF NATIVE CHICKEN IN WESTERN TAMIL NADU* - S. Satheeskumar; R. Prabakaran; N. Kumaravelu; S. Ezhilvalavan; A. Serma Saravana Pandian (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was conducted on intensive rearing of native chicken in three districts of Western Tamil Nadu viz., Erode, Tirupur and Coimbatore. The farms were selected by simple random sampling and data collected through a structured questionnaire.  A total of 60 farms, 20 in each district were surveyed for the purpose, out of which 22 were small, 15 medium and 23 large size farms with a capacity of less than 1000, 1001-2000 and above 2000 birds in each, respectively.  It was found that the farmers rearing native chicken intensively were predominantly young, had education upto school level, owned their farms individually and started the practice to earn subsidiary income. The small and medium size farms were mostly dependent on family labour, while hired labour was engaged in large farms.  Labour efficiency was found to improve with increasing farm size.